Catalogue. The Art Department and the Museum - Anonymus, A.
No. 2 = Bust of a Sumerian Royal Personnage (probably a divinity!) ca. 2400 B. C. — No. 6 = Guard from Palace of Artaxerxes I at Persepolis ca. 450 B. C.